Pengaruh Pendapatan Asli Daerah, Ukuran Pemerintah, dan Belanja Pemerintah Terhadap Pelaksanaan Internet Financial Reporting Pemerintah Provinsi di Indonesia - Sri Wahyuni Wulandari; Erna Sulistyowati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Internet financial reporting is crucial to raising public confidence and is one of the ways to maintain clean and good governance. The government has issued regulations on Internet Financial Reporting but has not been fully implemented by the district/city and province governments. Earlier studies indicated that local real income (PAD), government size, and regional spending influenced the implementation of Internet Financial Reporting but the results were inconsistent. The study aims to find out the impact between PAD, government size, and regional spending on the implementation of Internet Financial Reporting. The samples in this study consisted of 33 data obtained using purposive sampling techniques from 38 provinces, with observation time ranges from 2020 – 2022. The analysis of this study uses a double linear regression method using SPSS 22 software. Research results show that PADs and government measurements influence Internet Financial Reporting, but regional spending has no influence over the implementation of Internet financial reporting by the provincial government in Indonesia.